2021
DOI: 10.3390/molecules26247538
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin Complexed Lipid Nanoparticles of Irbesartan for Oral Applications: Design, Development, and In Vitro Characterization

Abstract: Irbesartan (IR) is an angiotensin II receptor antagonist drug with antihypertensive activity. IR bioavailability is limited due to poor solubility and first-pass metabolism. The current investigation aimed to design, develop, and characterize the cyclodextrin(s) (CD) complexed IR (IR-CD) loaded solid lipid nanoparticles (IR-CD-SLNs) for enhanced solubility, sustained release behavior, and subsequently improved bioavailability through oral administration. Based on phase solubility studies, solid complexes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 55 publications
1
12
2
Order By: Relevance
“…However, the scanning electron micrograph of the physical mixture demonstrated that IR remained dispersed and physically adsorbed on the surface of HPβCD not shown), signifying no physical complexation. This could have contributed to the faster dissolution profiles, reported in our earlier investigation [18]. The results were consistent with earlier published scanning electron micrographs.…”
Section: Sem Analysissupporting
confidence: 93%
“…However, the scanning electron micrograph of the physical mixture demonstrated that IR remained dispersed and physically adsorbed on the surface of HPβCD not shown), signifying no physical complexation. This could have contributed to the faster dissolution profiles, reported in our earlier investigation [18]. The results were consistent with earlier published scanning electron micrographs.…”
Section: Sem Analysissupporting
confidence: 93%
“…Meanwhile, the release of the drug can be termed as the first order when the rate of the release of the drug is a function of the remaining concentration of the drug [ 63 ]. The Higuchi model for the release kinetics states that the rate of the release of the drug is a function of the square root of the time [ 41 , 64 ]. Lastly, Korsmeyer–Peppas is a semi-empirical model that can usually be used to describe the mechanism of the drug release phenomenon consisting of diffusion or swelling [ 41 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The MOX-NE and MOX-NEM formulations were evaluated for their DS, PDI, and ZP using a Zetasizer instrument (Nano ZS Zen3600, Malvern Panalytical Inc., Westborough, MA, USA) at 25 • C in disposable, folded, clear, solvent-resistant micro cuvettes (ZEN0040) [31].…”
Section: Measurement Of Droplet Size (Ds) Polydispersity Index (Pdi) ...mentioning
confidence: 99%